A critical realist method for applied business research. Issue 2 (15th March 2018) - McAvoy, John; Butler, Tom
ABSTRACT: While the business research community has moved from describing critical realism as simply a compromise philosophy between positivists and interpretivists to its acceptance in its own right, it still lacks a choice of methods or processes for the business researcher to utilize. This paper presents a proposed method that can be used by business researchers who follow the critical realist paradigm. It explores the suitability of a critical realist approach to applied business and the importance of combining the ontological and epistemological elements described. The relevance of the search for causal mechanisms is shown and it is argued that this search benefits from the use of retroduction and retrodiction. A 'causal framework' is proposed as an optional artefact in the critical realist business researcher's 'toolkit' and a three step process is described, which uses causal frameworks to guide analysis.